2008
DOI: 10.1002/jmv.21166
|View full text |Cite
|
Sign up to set email alerts
|

Cervical and oral human papillomavirus types in HIV‐1 positive and negative women with cervical disease in South Africa

Abstract: This study tested cervical and oral human papillomavirus (HPV) infection in HIV-1 seropositive (HIV+) and seronegative (HIV-) women to determine any association between infections at both sites and the difference in prevalence of the HPV types infecting these women. Participants were 115 women referred to a colposcopy clinic after diagnosis of abnormal cervical cytology. The women showed low grade cervical intraepithelial neoplasia (CIN1) or high grade disease (CIN2/3) or no CIN based on colposcopy and histolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
3
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 20 publications
(33 reference statements)
4
43
3
2
Order By: Relevance
“…Today, it is clear that a woman can harbour multiple HPV infections with different oncogenic types. 25,26 Conclusion HPV infections were highly prevalent in this study of women without cervical cytological abnormalities. The most prevalent HPV types were HPV 62, 84 and 16.…”
Section: Infection With Multiple Human Papillomavirus Typesmentioning
confidence: 69%
See 1 more Smart Citation
“…Today, it is clear that a woman can harbour multiple HPV infections with different oncogenic types. 25,26 Conclusion HPV infections were highly prevalent in this study of women without cervical cytological abnormalities. The most prevalent HPV types were HPV 62, 84 and 16.…”
Section: Infection With Multiple Human Papillomavirus Typesmentioning
confidence: 69%
“…25,26 There has been a rise from 4% to 15.7% in multiple HPV infections found in cervical cancer in the past 20 years. 25 However, from the results of one study, it did not seem as if multiple HPV infections had an influence on the natural history of one another.…”
Section: Infection With Multiple Human Papillomavirus Typesmentioning
confidence: 99%
“…Known risk factors for oral and oropharyngeal HPV infection currently include lifetime number of sexual partners, [6,9,11] number of oral sex partners, [1,12] substance use [9,[12][13][14] and infection with HIV. [15][16][17][18] Sexual contact, either genital or oral, remains the primary mode of HPV transmission, and it is well documented that having multiple partners increases the prevalence of oral and genital HPV. [6,9,19,20] A study in KwaZulu-Natal, SA, reported male undergraduate students to have had a median of four sexual partners in the previous year.…”
Section: Discussionmentioning
confidence: 99%
“…Alguns autores demonstraram que, em comparação com as soronegativas, as mulheres HIV soropositivas são, aproximadamente, quatro vezes mais propensas a serem infectadas pelo HPV e cinco vezes mais a desenvolver CIN, além de lesões em múltiplos sítios, como vagina, vulva e região perianal (1,8,10,15) . Em nosso estudo, 19 (58%) em 33 lesões de colo uterino do grupo A correspondiam a CIN, o que demonstra frequência média maior do que a da literatura.…”
Section: Discussionunclassified
“…Torna-se relevante identificar a infecção epitelial genital pelo EBV, bem como a possível coinfecção com o HPV, principal agente associado ao desenvolvimento de lesões intraepiteliais e carcinomas escamosos genitais (17,19) . O imunocomprometimento relacionado com o vírus da imunodeficiência humana do tipo 1 (HIV-1) é sabidamente um fator de aumento do risco para a carcinogênese genital, assim, torna-se relevante verificar possíveis diferenças entre os pacientes (13,15) . Partindo desses pressupostos, os objetivos deste estudo foram verificar a frequência de imunopositividade para a LMP1 e do antígeno comum do HPV em lesões genitais provenientes de pacientes infectados ou não pelo HIV-1 e correlacionar a imunopositividade com o local e o diagnós-tico histopatológico das lesões.…”
Section: Investigation Of the Lmp1 Ebv And Co-infection By Hpv In Genunclassified